2014
DOI: 10.17221/216/2013-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Virulence surveys of wheat leaf rust in the Czech Republic and resistance genes in registered cultivars

Abstract: Hanzalová A., Bartoš P. (2014): Virulence surveys of wheat leaf rust in the Czech Republic and resistance genes in registered cultivars. Czech J. Genet. Plant Breed., 50: 241-246.The technical report presents a summary of results obtained in the leaf rust race surveys carried out in Czechoslovakia/Czech Republic in the years 1966-2001. The physiologic races were determined using the standard differentials Malakoff (Lr1), Carina (Lr2b), Brevit (Lr2c), Webster (Lr2a), Loros (Lr2c), Mediterranean (Lr3), Hussar (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…In this way we recorded similar races like those described in our previous report (Hanzalová & Bartoš 2014). Pathotype numbers 1, 4 and 5 in Table 3 correspond to race 61 common in previous years.…”
Section: /11supporting
confidence: 82%
See 2 more Smart Citations
“…In this way we recorded similar races like those described in our previous report (Hanzalová & Bartoš 2014). Pathotype numbers 1, 4 and 5 in Table 3 correspond to race 61 common in previous years.…”
Section: /11supporting
confidence: 82%
“…
AbstractHanzalová A., Bartoš P. (2014): The virulence spectrum of the wheat leaf rust population analyzed in the Czech Republic from 2002 to 2011. Czech J. Genet.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…McCallum et al (2011) found that the most common races in Canada during 2008 growing season were TDBJ (23.6%), TDBG (23.1%) and MLDS (18.9%). Moreover, Hanzalova and Bartos (2014) found that the leaf rust races 14, 77, 61, 53 and 2 were dominated in Czechoslovakia/Czech Republic in the years 1966-2001. Finally, Anjum et al (2014 identified the two leaf rust races 12-9 (93R37-1) and 77-11 (125R28) in India during 2009 growing season.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as the prevalence of races in a specific season and region depends on the type of wheat cultivars grown and to some extent on the predominant environmental conditions, especially temperature (Roelfs et al, 1992). Also, due to the long-distance dispersal of leaf rust races (intercontinental migration) (Burdon and Silk, 1997;Kolmer, 2005;Hanzalova and Bartos, 2014). This process led to the shifts in the genetic structure of the recipient pathogen population, especially when such pathogen cannot survive the summer in the country (Saari, 1976;Burdon and Silk, 1997).…”
Section: Discussionmentioning
confidence: 99%